Prácticas administrativas y su relación con el cumplimiento de objetivos organizacionales en las Pymes comerciales : Caso tres comisariatos del cantón La Maná. - Cunuhay Sigcha, Luis Adrian (2022)
At present, SMEs are an important and indispensable engine for the development of the economy in the countries, the development of SMEs is the development of the country. It is necessary to recognize that many SMEs do not have correct guidelines for their operation, the empiricism in the administrative practices that are performed and in many cases nonexistent is obvious, this seriously affects the companies to fulfill their objectives if they have established them. It is important to study the administrative practices and their relationship with the fulfillment of organizational objectives in commercial SMEs, taking as reference the case of three grocery stores of La Maná canton. The theoretical methodology with the historical-logical, synthetic analytical, deductive and hypothetical-deductive methods, also the quantitative empirical method, all focused on a descriptive and correlational scope. Bibliographic research was in addition used to support the theoretical information, while field research was used to collect information in each of the selected SMEs, through the application of instruments previously developed and approved by experts. Through interviews with managers and a census of collaborators, it was possible to identify certain deficiencies in administrative practices such as inadequate socialization of information, nonexistent manual of functions, little participation of personnel in decision making, dissatisfaction with the process of evaluation and control of labor performance and dissatisfaction with the existing recognitions and sanctions, also influencing the fulfillment or not of organizational objectives. For this reason, it is proposed an Organizational management model focused on the fulfillment of organizational objectives of the commercial SMEs of La Maná canton, providing a direct benefit to the organizations involved and to those who make them up, besides being useful to SMEs that share similar characteristics.